Ressenya d’En la pell del pacient, de Salvador Esquena (Ara Llibres, Barcelona, 2016, 184 pàgines) - Adéla Kotátková (Ítaca)
Ressenya d’En la pell del pacient, de Salvador Esquena (Ara Llibres, Barcelona, 2016, 184 pàgines).